Risk factors and complications during operations on abdominal organs in patients with cirrhosis of the liver (Eurasian Research Bulletin, 2022)
This review presents an analysis of risk factors and characteristic complications of extrahepatic abdominal surgery in patients with cirrhosis of the liver. Portal hypertension, edematous-ascitic syndrome, spontaneous bacterial peritonitis, hepatorenal syndrome, and hepatic encephalopathy are poor predictors. Сonsideration and analysis of which will predict and prevent complications, as well as improve the effectiveness and results of treatment. This review represents a set of practical algorithms whose basis is the most effective methods to diagnose, treat, and prevent complications of cirrhosis.